Acculturation of Javanese-Islamic Culture in the Tradition of Pitonan Babies in Wongsorejo Village, Banyuwangi: Roland Barthes' Semiotic Analysis - Ana Nur Jannah; Moh. Syamsul Ma’arif (Universitas Negeri Semarang, 2026)
The pitonan baby tradition is one of the birth rituals in Javanese culture that continues to be practiced from generation to generation and contains various symbols that represent the community's social, spiritual, and religious values. Over time, this tradition has undergone acculturation between Javanese culture and Islamic teachings, a process that occurs adaptively through the reinterpretation of traditional symbols. This study aims to analyze the symbolic meanings and forms of Javanese–Islamic cultural acculturation in the pitonan baby tradition in Wongsorejo Village, Banyuwangi, using Roland Barthes's semiotic approach. This research employs a descriptive qualitative method with an interpretative orientation. Data were collected through in-depth interviews with key informants, participant observation of the implementation of the pitonan baby ritual, and visual documentation supported by field notes. Data analysis was conducted using the interactive model of Matthew B. Miles and A. Michael Huberman, which includes data reduction, data display, and conclusion drawing. The interpretation of symbols was carried out through denotative, connotative, and mythological analyses to reveal ideological meanings within cultural practices. The findings indicate that symbols in the pitonan tradition, such as tujuh kulub, iwel-iwel, red and white jenang, nasi buceng, the ritual of stepping on jenang, and the object-selection procession, represent a dynamic process of Javanese–Islamic cultural acculturation. This acculturation process is characterized by three main forms: reinterpretation of symbolic meanings in elements such as tujuh kulub, jenang, and tumpeng; partial resistance to earlier belief elements found in iwel-iwel and the stepping-on-jenang ritual; and selective elimination of elements considered inconsistent with the value of tauhid, such as fortune-telling interpretations through object selection. In addition, the role of the kiai as an agent of cultural reinterpretation is significant in directing the transformation of symbolic meanings toward Islamic values. The pitonan baby tradition is no longer understood as a magical practice but rather as a medium of prayer, gratitude, and reinforcement of the value of tauhid within community life. This study contributes theoretically to the development of cultural semiotic studies and enhances understanding of symbolic negotiation processes within Javanese–Islamic cultural acculturation.